Exchange Rate Exposure and Optimal Hedging Strategies when Interest Rates are Stochastic: a Simulation-Based Approach - Castillo R., Augusto (Estudios de Administración, 2003)
In this paper i analyze the problem faced by an investor expecting to receive a cash flow in a foreign currency. The investor is assumed to be exposed to long-term exchange rate risk, having no access to long-term forward contracts to hedge perfectly. Under non stochastic interest rates the investor is able to hedge perfectly using short-term forward contracts, but perfect hedging is not possible when we consider interest rates to be stochastic. I present here a simulation-based methodology to obtain optimal hedging under stochastic interest rates (i.e. when perfect hedging can not be reached). Then, i explore how we quality of the hedging to be reached depends on some key factors such as the volatility of the exchange rate, the volatility of the interest rates, and the degree of correlation among the stochastic variables considered.